Female levator ani muscle damage assessment in supine and upright position - Irina de Alba Alvarez; Annemarie van der Steen; Anique T.M. Grob; Frieda van den Noort (Scientific Reports)
Abstract There is damage in the pelvic floor only visible in upright imaging. This damage have not been yet studied. The aim of this research is to assess the difference in levator ani muscle (LAM) damage in supine and upright position by means of MRI scans. Sixty-four patients with minimum stage 2 prolapse of the anterior vaginal wall or uterus, without previous pelvic organ prolapse (POP) surgery were scanned in a MR scanner in supine and upright position. Damage to the pubococcygeus muscle (PCM) and the iliococcygeal muscle (ICM) was scored as none, minor or major. For PCM, a previously established protocol was used. For ICM, a protocol for damage assessment was established and validated in this study, by determining the interclass correlation coefficient (ICC). The new ICM assessment protocol was established with ICC values of 0.68 (0.57–0.77) for supine and 0.81 (0.74–0.86) for upright assessment. 6.3% major ICM damage was found in supine vs. 51.6% in upright position with a significant difference of p < 0.001 for the sign-test. There was an underestimation of ICM damage in 59% of the cases in supine position. PCM damage scoring was not feasible on upright MRI’s and therefore only assessed on supine scans. In our POP population we found 53.1% of the women with major damage to either the PCM or ICM and 32.8% with major damage in both, leading to a total of 85.9% of women with major damage to at least one structure. There is a significant difference in LAM damage assessment between supine and upright position. Supine imaging leads to a severe underestimation of ICM damage while for the PCM supine damage assessment remains superior.